Frequency of Thyroid Lesions at Pathology Department of King Edward Medical University Lahore - Zahid Mahmood Akhtar, Madiha Arshad, Rabia Altaf (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Thyroid gland is notorious for carrying commonest endocrine pathologies and also for commonest endocrine malignancy. It is the 5th most common cancer in human beings. This makes to carry out current study to get insight of frequency of thyroid lesions at tertiary care level. Methods: This was a descriptive cross-sectional study. The study was done at the Department of Pathology, King Edward Medical University Lahore with the collaboration of four surgical units of Mayo Hospital Lahore from 2010 to 2019. Total 1601 cases were included. Information about age, sex and diagnosis was entered in the pre designed proforma. SPSS version 22 was used for data analysis. Descriptive analysis was done and the results were presented as frequencies, percentages and ratios. The results were then studied against local and international data. Results: This study revealed non neoplastic and neoplastic lesions as 1323 (82.63%) and 278 (17.37%) respectively. Bulk of the lesions 61.6% were between the age bracket of 20-39 years. Mean±SD for age was 34.22±11.42 years. Female to male ratio(F:M) was in favour of females as 9.81:1. Among the non neoplastic lesions, MNG 1151(87%) was a dominant lesion followed by TH 82(6%). LT 29(2.19%) and HT 26(1.96%) were other important lesions. F:M ratio was 10.80:1. Neoplastic lesions were divided into benign 178(64%) and malignant tumors 100(36%). FA was the leading benign neoplasm 164(59%). Rest of the benign tumors shared a minor fraction except HCA 12(4.31%). Among the malignant category, Papillary carcinoma 69(24.82%) dominated over MC 12(4.31%). FC 7(2.51%) and AC 6(2.15%) were other significant findings. F:M ratio in malignancy was 3.16:1 which was significantly lower than 13.83:1 in benign tumors. Conclusion: MNG is the dominant lesion among the non neoplastic lesions while in the neoplastic category FA was leading as benign neoplasm. Papillary carcinoma turned out to be the commonest malignant tumor. Major share of all the lesions were seen between 20-39 years.